2000
DOI: 10.1093/brain/123.11.2189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the decision-making deficit of patients with ventromedial prefrontal cortex lesions

Abstract: On a gambling task that models real-life decisions, patients with bilateral lesions of the ventromedial prefrontal cortex (VM) opt for choices that yield high immediate gains in spite of higher future losses. In this study, we addressed three possibilities that may account for this behaviour: (i) hypersensitivity to reward; (ii) insensitivity to punishment; and (iii) insensitivity to future consequences, such that behaviour is always guided by immediate prospects. For this purpose, we designed a variant of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,283
14
41

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,629 publications
(1,411 citation statements)
references
References 47 publications
57
1,283
14
41
Order By: Relevance
“…It appears that individuals with right OFC dysfunction, which include cocaine abusers, may not make associations between present emotions and past negative experiences, despite knowing the adverse consequences (Bechara, 2000b). Therefore, understanding the roles of the OFC and DLPFC in relation to substance abuse could facilitate the development of more appropriately targeted prevention and treatment programs for those who suffer from addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that individuals with right OFC dysfunction, which include cocaine abusers, may not make associations between present emotions and past negative experiences, despite knowing the adverse consequences (Bechara, 2000b). Therefore, understanding the roles of the OFC and DLPFC in relation to substance abuse could facilitate the development of more appropriately targeted prevention and treatment programs for those who suffer from addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies show that the OFC plays an important role in the ability to perform well on this task (Bechara et al, 2000b). The Iowa Gambling Task measures the participant's ability to choose between high gains with a risk of extremely high losses, and low gains with a risk of smaller losses.…”
Section: Iowa Gambling Task (Active Task)mentioning
confidence: 99%
“…Both lesion and neuroimaging studies suggest that the VMPFC, amygdala and nucleus accumbens are part of a neural network that is crucial for advantageous decisionmaking. [38][39][40][41][42][43] The current psychological model of compulsive hoarding emphasizes information processing deficits including decision-making. 1 Indeed, deciding what to keep and what to discard can be an extremely difficult task for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found psychopathic adults to perform similarly to comparison groups on the gambling task [60,12]. However, the studies contained significant procedural differences from those presented by Bechara et al [8]. Furthermore, in a recent study using identical instructions to those of Bechara et al [6], Blair et al found that the performance of boys with psychopathic tendencies on the gambling task was impaired relative to a comparison group [14].…”
Section: Introductionmentioning
confidence: 99%